2012
DOI: 10.1371/journal.pone.0043213
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Nanosecond Pulsed Electric Fields Combined with Low Concentration of Gemcitabine on Human Oral Squamous Cell Carcinoma In Vitro

Abstract: Treatment of cancer often involves uses of multiple therapeutic strategies with different mechanisms of action. In this study we investigated combinations of nanosecond pulsed electric fields (nsPEF) with low concentrations of gemcitabine on human oral cancer cells. Cells (Cal-27) were treated with pulse parameters (20 pulses, 100 ns in duration, intensities of 10, 30 and 60 kV/cm) and then cultured in medium with 0.01 µg/ml gemcitabine. Proliferation, apoptosis/necrosis, invasion and morphology of those cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 52 publications
(70 reference statements)
1
56
2
Order By: Relevance
“…Recent studies showed that nsPEFs could enhance the efficacy of chemotherapeutic drugs in vitro , such as gemcitabine and pingyangmycin323334. Thus, we speculate that nsPEFs might improve the therapeutic effect of the mTOR inhibitor everolimus in melanoma.…”
mentioning
confidence: 80%
“…Recent studies showed that nsPEFs could enhance the efficacy of chemotherapeutic drugs in vitro , such as gemcitabine and pingyangmycin323334. Thus, we speculate that nsPEFs might improve the therapeutic effect of the mTOR inhibitor everolimus in melanoma.…”
mentioning
confidence: 80%
“…The nsPEF generator was applied as previously described54. Digital phosphor oscilloscope (DPO4054, Tektronix) with a probe (P6015A, Tektronix) was utilized to monitor the voltage waveform.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported necrosis due to the colloid-osmotic cell swelling as a predominant mechanism of cell death after exposure to nsEP5610212223. This mechanism could be blocked by isosmotic addition of a nanopore-impermeable solute (such as sucrose) to the growth medium32.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, several groups including ours reported that cells exposed to nsEP swell and may die because of necrosis within the first several hours after the treatment5610212223. Necrosis is caused by the presence of long lived nanopores and colloid-osmotic imbalance which leads to cell swelling and membrane rupture.…”
mentioning
confidence: 81%